Peningkatan Kompetensi Menerapkan Microsoft Office 365 Dalam Pembelajaran Abad 21 Dimasa Pandemi Melalui IHT - Menik Mustikatun (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study was to find out whether the implementation of IHT which was carried out programmatically by researchers could improve the competence of teachers to apply Microsoft Office 365 in 21st century learning at SMP Negeri 3 Rembang in implementing online learning during the COVID-19 pandemic. The research subjects were all teachers of SMP Negeri 3 Rembang. The research time is for six months, starting from January to June 2021. Each cycle consists of 4 stages of activities, namely planning, implementing actions, observing and reflecting. In the implementation of IHT actions in each cycle, there was an increase in the average competence of teachers in implementing Microsoft Office 365 in 21st century learning during the pandemic, namely from 2.30 with sufficient category (C+) in the pre-cycle, increasing 0.59 points to 2.89 with good category (B) in the first cycle, and then increased again by 0.31 points to 3.20 with category B+ in the second cycle. Implementation of the IHT action in each cycle, there was an increase in the activity of researchers in conducting IHT for teachers of SMP Negeri 3 Rembang, from 2.74 with a good category (B-) in the first cycle, and then increased by 0.82 points to 3.56 with very good category (A-) in cycle II. In the implementation of the IHT action in each cycle, there was an increase in teacher activity at SMP Negeri 3 Rembang, from 66.67% in the active category or 2.67 in the good category (B-) in the first cycle, then increased by 25.92% to 92 .59% in the very active category or an increase of 1.03 points to 3.70 in the very good category (A-) in the second cycle.